2022
DOI: 10.1002/ces2.10132
|View full text |Cite
|
Sign up to set email alerts
|

Bubble generation in refractory porous plugs: The role of the ceramic surface composition

Abstract: Porous ceramic plugs are refractory devices applied in the steel ladle to inject gas bubbles into the liquid metal, aiming at its chemical and thermal homogenization, and the removal of non-metallic inclusions. Regarding its wear and corrosion resistance, the plug composition typically exhibits a low wettability by liquid steel to limit its infiltration into the porous structure. However, an additional aspect for the performance of plugs is their ability to control the size of the generated bubble, maximizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…They pointed out that the number of active sites increases with increasing gas injection flow rate, permeability, the velocity of the downward‐flowing water, and lower contact angle. Falsetti et al [ 13 ] injected gas into liquid media through ceramic capillary structures and studied the influence of the pore size and the contact angle upon the size of the generated bubble. Their results indicated the composition of the ceramic plug's surface could change the contact angle, thus affect the bubble size.…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out that the number of active sites increases with increasing gas injection flow rate, permeability, the velocity of the downward‐flowing water, and lower contact angle. Falsetti et al [ 13 ] injected gas into liquid media through ceramic capillary structures and studied the influence of the pore size and the contact angle upon the size of the generated bubble. Their results indicated the composition of the ceramic plug's surface could change the contact angle, thus affect the bubble size.…”
Section: Introductionmentioning
confidence: 99%
“…Cherniak et al [ 11 ] found that the diffusion rate of a light REE was much slower than that of heavy REE, and the diffusion of REE required higher diffusion activation energy. Falsetti et al [ 12 ] studied the effects of ceramic porosity and contact angle on ceramic refractories and found that ceramic refractories in contact with molten steel usually exhibit high contact angles to avoid liquid penetrating the pores. From previous studies, we found that element diffusion had a good relationship with temperature, pressure, and its own physical and chemical properties, which is a good topic for the study of element diffusion.…”
Section: Introductionmentioning
confidence: 99%